Prevalence of Musculoskeletal Pain in Rural Workers: A Review of the Literature (Research, Society and Development, 2021)
Introduction: In order to accompany the changes that occur in the rural sector as a result of technological advances, ergonomic and postural adaptations are required in the workplaces, directly interfering with their forms of work and production. Objective: To analyze bibliographically the rates of prevalence of DME in rural workers. Materials and methods: In all, 831 scientific productions were found on the prevalence of DME in farmers in the last five years. After excluding duplicates and productions that weren’t related to the proposed theme, 55 scientific productions in full that met the inclusion criteria were analyzed, of which 35 contributed to answer the guiding question of this review. As for the prevalence of DME, results were found that demonstrate a higher prevalence of DME in the spine, with a higher incidence on the lumbar spine, on the shoulder and on the knee in the analyzed rural workers. Conclusion: The study made it possible to identify a high prevalence of DME in rural workers. However, it cannot be said that this population is more affected by DME when compared to populations from other sectors of work.